Wilson’s disease- A neurodegenerative disease - Sekaran, Vidhya Guna (Indian Journal of Case Reports, 2025)
Wilson’s disease (WD) (hepatolenticular degeneration) is a rare autosomal recessive disorder caused by mutations in the ATP7B gene. Copper concentration in the liver is a diagnostic and prognostic indicator for the disease. Here, I present the case of a 52-year-old male, a known chronic smoker, who presented with a history of recurrent backwards falls, slowness of all activities, head titubation, slurred speech, and tremors of the right upper limb and both lower limbs. Normal hepatic copper levels typically range from 15 to 55 μg/g dry weight. Neurological assessment revealed +2 in deep tendon reflexes, and cerebellar function tests showed that there were involuntary, irregular, rhythmic coarse tremors of both upper and lower limbs, diadochokinetic, and impaired tandem walking. WD was identified, and he was started on chelation therapy and a metallothionein inducer to inhibit intestinal absorption and fecal excretion of copper. Hence, highlighting this case helps to understand the originality of the patient’s condition.